The Moderating Influence of Heart Rate Variability on Stressor-Elicited Change in Pupillary and Attentional Indices of Emotional Processing: An Eye-Tracking Study - Macatee, Richard J. (Biol Psychol, 2016)
Low resting heart rate variability (HRV) is associated with a broad array of negative psychosocial outcomes. Recent theoretical explications of HRV suggest it is an autonomic marker of emotion regulation capacity, but limited research has examined its relationship with emotional information processing indices. The present study utilized eye-tracking methodology to test HRV’s theorized role as a marker of emotion regulation capacity in a non-clinical sample. Attentional biases towards threatening, dysphoric, and positive emotional information as well as affective modulation of pupil size were assessed before and after a stress induction. Low resting HRV marginally predicted larger increases in attentional bias towards positive emotional stimuli from pre to post-stress induction and significantly predicted decreased pupil dilation to positive stimuli after the stress induction only; exploratory analyses suggested that this pattern might reflect an unsuccessful attempt at anxious mood repair. HRV was unrelated to negative emotional information processing. Findings are consistent with existing theories of HRV’s psychological significance and suggest a specific association with altered positive emotional processing under acute stress.